Together - Sellers, Debra M. (My University, 2008)
This creative work consists of a photograph and accompanying poem through which the reader is encouraged to examine stereotypes of death and to creatively explore beliefs concerning love and spirituality. Although cemeteries appear to be the theme of the photograph, the poem speaks of the people represented by the gravestones and of the possibility of everlasting love and loyalty between two individuals.
Keywords: Death; Cemetery; Gravestone; Spritual